2022
DOI: 10.1108/hff-02-2022-0106
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection process endorsed in coaxial duct with Soret/Dufour effect

Abstract: Purpose The purpose of this paper is to analyse the buoyancy flow, mass and heat transfer in coaxial duct under Soret and Dufour effect. The combined effects of the thermal-diffusion and diffusion-thermo coefficients, as well as the Schmidt number, on natural convection in a heated lower coaxial curve were explored using the proposed physical model. The Dufour and Soret effects are taken into consideration in the energy and concentration equations, respectively. Design/methodology/approach The dominating mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…They showed that the presence of alumina nanoparticles at low increasing concentrations favors the average Nusselt number. The injection of nanoparticles in the base fluids has considerably improved the thermal transfer in different applications, which is why its use is noted in very recent works [37][38][39][40] In recent years, MHD flows have been the subject of several research works. Pordanjani et al [41] analyzed the natural convection of a nanofluid flow in a square tank with a fin.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the presence of alumina nanoparticles at low increasing concentrations favors the average Nusselt number. The injection of nanoparticles in the base fluids has considerably improved the thermal transfer in different applications, which is why its use is noted in very recent works [37][38][39][40] In recent years, MHD flows have been the subject of several research works. Pordanjani et al [41] analyzed the natural convection of a nanofluid flow in a square tank with a fin.…”
Section: Introductionmentioning
confidence: 99%
“…Sarkar et al (2021) scrutinized the thermal convection in an air-filled semi-elliptical cavity with a heated flat bottom and a cold curved wall and found that the flow controlling and geometric parameters affect the formation of multicellular vortices. Buoyant flow, mass and heat transfer analysis in a coaxial duct are explored by Shah et al (2022), who reported that the thermal behavior is markedly affected by the flow-controlling parameter. Ridouane and Campo (2006) compared thermal convection in circular and square cavities and concluded that heat transfer enhancement is only obtained with circular cavities at the lower Rayleigh numbers (Ra).…”
Section: Introductionmentioning
confidence: 99%